2021
DOI: 10.1089/wound.2020.1218
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Assessment of Single-Use Negative Pressure Wound Therapy During In Vivo Porcine Wound Healing

Abstract: Traditional negative pressure wound therapy (tNPWT) systems can be large and cumbersome, limiting patient mobility and adversely affecting quality of life. PICOÔ, a no canister single-use system, offers a lightweight, portable alternative to tNPWT, with improved clinical performance. The aim of this study was to determine the potential mechanism(s) of action of single-use NPWT (sNPWT) versus tNPWT. Approach: sNPWT and tNPWT were applied to an in vivo porcine excisional wound model, following product use guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Further, tNPWT‐induced inflammation led to elevated epidermal apoptosis and epidermal‐dermal junction break down, not dissimilar to that observed following pressure injury 39 . Matrix metalloproteinase levels were also higher following tNPWT, as shown in our previous in vivo study, 35 suggesting the potential to contribute to delayed healing via excessive proteolysis of matrix components 40 . Collectively, our ex vivo findings suggest that sNPWT beneficially alters multiple aspects of wound edge physiology vs tNPWT, and this may confer improved clinical efficacy.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Further, tNPWT‐induced inflammation led to elevated epidermal apoptosis and epidermal‐dermal junction break down, not dissimilar to that observed following pressure injury 39 . Matrix metalloproteinase levels were also higher following tNPWT, as shown in our previous in vivo study, 35 suggesting the potential to contribute to delayed healing via excessive proteolysis of matrix components 40 . Collectively, our ex vivo findings suggest that sNPWT beneficially alters multiple aspects of wound edge physiology vs tNPWT, and this may confer improved clinical efficacy.…”
Section: Discussionsupporting
confidence: 68%
“…However, these reports have largely focused on the effects of sustained compression and damage at the wound bed: foam filler interface. Retention of wound filler can also increase inflammatory cell influx and promote foreign body reactions 12,34,35 . Our data now suggest the importance of considering wound‐edge epidermal‐derived inflammatory mediators.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Contemporary dressings contain a myriad of material properties to aid tissue repair and incorporate substances with known pro-healing or antimicrobial effects [202,203]. More advanced solutions are available, including the continually evolving negative pressure wound therapy modality [204]. Despite numerous available treatments, current best practice wound management is almost exclusively aimed at addressing secondary causes of chronicity, while also relying heavily on patient compliance.…”
Section: Current Therapies and Future Opportunitiesmentioning
confidence: 99%
“…A recent preclinical study 15 confirmed the results of the clinical trial and found that the s-NPWT used in that study improves multiple aspects of healing versus t-NPWT and promotes faster healing. The area of the wound remaining open, determined as a percentage of day 0 wound area, was significantly smaller following s-NPWT than t-NPWT at both day 6 (70.06% vs. 78.55%; p < 0.001) and day 12 (18.56% vs. 33.36%; p < 0.001) postinjury.…”
Section: Discussionmentioning
confidence: 62%